Usability of academic management system - Wan Hassan, Wan Azlan; Ahmad Teridi, Norhawani; Abdullah, Khairul Annuar; Hamid, Azhar; Jusoff, Kamaruzaman; Megat Mohd Zainuddin, Norziha (Canadian Research & Development Center of Sciences and Cultures, 2011)
The usability of system lies on the effectiveness and ease-of-use of a system. The main function of Academic Management System (AMS) is to assist university staff to manage students’ records. A student record embodies in various and numerous courses management, finance, examination, accommodation and other essential information. The purpose of this paper is to evaluate the concept of system usability. It subsequently observes and analyzes the usability of AMS at a university by applying Nielsen’s heuristic evaluation method. As a preliminary study, the usability of AMS at one of the Institute of Higher Learning (IHL) in Malaysia has been chosen and assessed. The results obtained can be served as comparative guides for future betterments and references to the IHL. The study shows that the usability constructs selected are not being fulfilled in AMS. Recommendations to improve the usability of AMS are also discussed.